An experimental study to improve filtration properties of water‑based drilling fluids using rambutan as green additive - Ikram, Rabia; Mohamed Jan, Badrul; Ahmad, Waqas; Metselaar, Hendrik Simon Cornelis; Sidek, Akhmal; Mohd Sarjidan, Mohd Arif; Kenanakis, George (Springer, 2024)
It is not a secret that the drilling process is crucial to ensure that the drilling liquid has the proper filtration properties to minimize damage to the formation. Over the years, eco-friendly and cost-effective additives have been added to drilling fluids to ensure that they have the desired rheological properties and comply with the required standards of the American Petroleum Institute (API). Rambutan waste, one of Malaysia’s most produced fruit wastes, was regarded for the first time as a filtering additive in water-based drilling fluids (WBDF). Rambutan peel contains cellulose fibers that act as rheology modifiers. Rambutan fiber increases the pressure on the crack of the plug and reduces the loss of liquids. Low, medium, and high concentrations of rambutan waste (0.01, 0.1, and 0.5 g) were used to prepare samples of mud to compare the rheological and filtration properties to those of water-based mud. In addition, rambutan waste biopowder has been characterized using X-ray diffraction (XRD), Fourier transformation infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and energy-dispersive X-ray spectroscopy (EDX) analysis. The results showed that by increasing the concentration of rambutan waste samples, the properties such as plastic viscosity (PV), yield point (YP), and gel strength (GS) are gradually increased. Furthermore, rambutan additives significantly improved the f iltering performance by reducing the loss of filters (FL) and the thickness of mud cakes (MCT). It was observed that 0.01 g of raw rambutan peel reduced FL from 9 to 4 ml compared to 9 ml of base liquid. In addition, the lowest concentration of rambutan additive produced the thinnest mud cake of 1.09 mm compared to 2.82 mm of base liquid, respectively. On the basis of promising results, low amounts of bio-waste are recommended as green additives to improve the rheological and filtration characteristics of drilling fluids.